Long‐term trends in fruit production in a tropical forest at Ngogo, Kibale National Park, Uganda. (17th February 2020) - Potts, Kevin B.; Watts, David P.; Langergraber, Kevin E.; Mitani, John C.
Abstract: Fruit production in tropical forests varies considerably in space and time, with important implications for frugivorous consumers. Characterizing temporal variation in forest productivity is thus critical for understanding adaptations of tropical forest frugivores, yet long‐term phenology data from the tropics, in particular from African forests, are still scarce. Similarly, as the abiotic factors driving phenology in the tropics are predicted to change with a warming climate, studies documenting the relationship between climatic variables and fruit production are increasingly important. Here, we present data from 19 years of monitoring the phenology of 20 tree species at Ngogo in Kibale National Park, Uganda. Our aims were to characterize short‐ and long‐term trends in productivity and to understand the abiotic factors driving temporal variability in fruit production. Short‐term (month‐to‐month) variability in fruiting was relatively low at Ngogo, and overall fruit production increased significantly through the first half of the study. Among the abiotic variables, we expected to influence phenology patterns (including rainfall, solar irradiance, and average temperature), only average temperature was a significant predictor of monthly fruit production. We discuss these findings as they relate to the resource base of the frugivorous vertebrate community inhabiting Ngogo.